The Somaliland's recognition: Challenges and opportunities - Abdillahi Yousuf Elmi (Juusto), (Technium Social Sciences Journal, 2025)
This paper intended to discuss the critical matters related to Somaliland's diplomatic recognition challenges and opportunities. These challenges stem from various historical, political, economic, and social factors that have shaped the region's quest for sovereignty, and analyses of these elements better explained the potential pathways for achieving international legitimacy and support for Somaliland's aspirations. After the collapse of Somalia's central government, Somaliland declared its independence in 1991 and successfully established government institutions that provide an efficient system of security and stability; however, Somaliland has not yet received international recognition.